2003
DOI: 10.1038/sj.hdy.6800190
|View full text |Cite
|
Sign up to set email alerts
|

Genetic effects on microsatellite diversity in wild emmer wheat (Triticum dicoccoides) at the Yehudiyya microsite, Israel

Abstract: This study investigated allele size constraints and clustering, and genetic effects on microsatellite (simple sequence repeat, SSR) diversity at 28 loci comprising seven types of tandem repeated dinucleotide motifs in a natural population of wild emmer wheat, Triticum dicoccoides, from a shade vs sun microsite in Yehudiyya, northeast of the Sea of Galilee, Israel. It was found that allele distribution at SSR loci is clustered and constrained with lower or higher boundary. This may imply that SSR have functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
3

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 47 publications
0
22
0
3
Order By: Relevance
“…Li et al (2003) examined microsatellite diversity in wild emmer wheat, and they found a strong effect of the interaction between mean repeat length and SSR locus distance from the centromere on the number of alleles, and variance in repeat size at SSR loci. Future studies should be performed to determine the location of Rops15 in the R. pseudoacacia genome.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al (2003) examined microsatellite diversity in wild emmer wheat, and they found a strong effect of the interaction between mean repeat length and SSR locus distance from the centromere on the number of alleles, and variance in repeat size at SSR loci. Future studies should be performed to determine the location of Rops15 in the R. pseudoacacia genome.…”
Section: Discussionmentioning
confidence: 99%
“…There were more motif combinations in B. napus (716) than in B. rapa (304) or B. oleracea (214). The generation of SSR diversity in plants is a complex process which is affected by genetic factors such as replication slippage, recombination effects and mutational mechanisms that could be induced by ecological stresses (Li et al 2003). Mononucleotide SSRs might be the original SSRs from which long and compound motif SSRs were derived.…”
Section: Discussionmentioning
confidence: 99%
“…Variation in SSRs arises due to mutation of the nucleotide sequence of the motifs and changes in the number of repeat units (Li et al 2003). In related species, SSR motifs are in general conserved, thus most of the SSR variation depends on the number of repeats (Vigouroux et al 2003;Asp et al 2007;Gao et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…They reside primarily within or near genes [96]. Unequal crossing-over may be one of the major mechanisms responsible for the variation and instability of microsatellite loci [97][98][99][100]. Since microsatellite loci are usually located near or within genes, unequal crossing-over between the short repeats in the microsatellites may lead to novel alleles at microsatellite loci and the gene loci involved.…”
Section: Unequal Crossing-overmentioning
confidence: 99%